HUBUNGAN IDENTIFIKASI PASIEN SECARA BENAR DENGAN KEPUASAN PASIEN DI INSTALASI GAWAT DARURAT UPTD RUMAH SAKIT MENEMBO-NEMBO BITUNG - Usman Kodobo; Sunarti Basso; Minar V.R.M Hutauruk (Jurnal Rumpun Ilmu Kesehatan, 2022)
The hospital is a health service institution that provides comprehensive health services that have a high risk of patient safety, patient companions, visitors, and human resources. The purpose of this study was to determine the relationship between correct patient identification and patient satisfaction in the uptd emergency department at the Menbo-nembo Bitung Hospital. Methods The design of this study used a descriptive analytic design with a cross sectional approach. The population is 998 respondents, the sample in this study is 99 respondents using a questionnaire measuring instrument. Then the data collected was analyzed using the Chi-Square test. With a significant value (a) 0.05. The results of the Chi-Square test showed that there were 0 cells that had an expected count value of less than 5, then the reading of the results was continued on the Fischer exact test with a p value = .000 where if the value was smaller than the value = 0.05. The conclusion in this study is that there is a relationship between correct patient identification and patient satisfaction in the uptd emergency department at the Menbo-nembo Bitung Hospital.